Uma sequência didática como desenvolvimento do ensino de energia na educação básica - Cavalcante, Rogério da Silva (2022)
This material represents the final product of a Professional Master's thesis in Physics Teaching carried out at the Federal University of Ceará, which aims to enhance the possibilities of the pedagogical work of Elementary School Science teachers through a teaching sequence for the development of teaching power. The teaching sequence consists of four stages. In each of them, a motivating text will be presented as a starting point for the development of the content, followed by targeted activities using the investigative learning approach. In this way, in addition to seeking to facilitate the teacher's pedagogical work, this didactic sequence also intends to offer the elementary school student the possibility of establishing a more concrete relationship with the concept of energy, always taking into account the heterogeneity of each group of students in which this sequence can be used. In this context, the teaching sequence is presented as a suggestion to support the teacher's work, aiming at the improvement of the teaching-learning process.